The contribution of Al-Oqbani in the advisory opinion blogs through the ones of Al-Wansharisi_Quantitative statistical study_: - szoubeyr, Salmi; belarbi, khaled (The Algerian Historical Journal, 2026)
The jurisprudence of advisory opinions are among the characteristics of the Maliki school in the Islamic Maghreb that show various daily issues that have arisen in people’s lives, which had to be on jurists legally rooted it from its original sources, such as judicial documents or scientific correspondence. These blogs have become sources to make regions and cities have history, because of the signals it contains on various issues. The most important of which is the arabised standard of Al-Wansharisi, that highlighted the importance of scientific centers and the phenomenon of scientific houses in the Maliki jurisprudential production in general, and the ones of the advisory opinions in particular, among of these houses is the one of Al-Oqbani Al-Tlemceni. In this regard, there is a variety of results, most importantly is: that the scholars of the house of Al-Oqbani had a significant contribution to the formulation of the standard code. Their advisory opinions reached 200 in various chapters.